The relationship between some teacher variables and teaching effectiveness in high school chemistry as measured by achievement test scores - Alicias, Teresita R. (Animo Repository, 1980)
This study identified some of the teacher variables that are related to success in teaching high school chemistry. The following teacher variables, namely: 1) civil status, 2) Civil service eligibility, 3) location of alma mater, 4) teaching load, 5) training in the use of the UPSEC (Chemistry for Philippine High Schools) book, 6) total teaching experience, 7) chemistry teaching experience, 8) units earned in chemistry, and 9) in-service training in chemistry/science were hypothesized to have a positive correlation with teacher success in teaching high school chemistry. The investigator randomly selected 30 teachers from the population of chemistry teachers of all public and private schools of Ilocos Sur during the school year 1978-1979. Barangay high schools were excluded from the population. A personal data questionnaire was developed and floated to gather data on the independent variables. A chemistry achievement test developed, validated, and administered by the investigator yielded the data on the criterion--success of teaching high school chemistry. The data were initially subjected to a correlational analysis each independent variable was correlated with the criterion. Point biserial correlation was used for the dichotomous variables Pearson's product-moment correlation was used for the continuous variables. Then the data were subjected to regression analyses--both ordinary and stepwise. The appropriate tests of significance were conducted in all instances where they were deemed necessary. In the light of the findings, the conclusions drawn were: 1) Experience is the only teacher variable that significantly relates with success in teaching high school chemistry. This variable has a two-fold nature. Each fold is related to the criterion in a different manner. Total teaching experience--a proxy for general experience--has a negative effect on teaching success. On the other hand, chemistry teaching experience--specific experience--has a positive effect on teaching success. 2) Variables such as units earne